"An orangutan stole my homework": Using NPR's "Bluff The Listener" to introduce narrative rationality. Issue 4 (2nd October 2022) - Murphy, Mollie K.; Seiter, John S.
Abstract : Courses: Rhetorical Criticism, Contemporary Rhetoric, Argumentation, Persuasion, Communication Theory. Objectives: Students will (1) learn the basics of the narrative rationality as a mode of judging rhetoric, and (2) observe the ways in which humans use narrative fidelity and narrative probability to judge stories.